Transformasi Digital UMKM Indonesia di Era Industri 5.0: Studi Kasus di Kota Banda Aceh - Salam, Abdus; Imilda (Jurnal Manajemen dan Teknologi, 2024)
Digital transformation of Micro, Small and Medium Enterprises (MSMEs) in Banda Aceh City is very important in adapting to the challenges and opportunities presented by the digital era. This research examines the processes, challenges and opportunities faced by MSMEs in adopting digital technology in the city of Banda Aceh. Through comprehensive analysis, this research aims to provide valuable insights for stakeholders, including the government, business actors and the general public. This study identified several challenges, including limited access to technological infrastructure, low levels of digital literacy, limited resources, data security issues, and dependence on conventional systems. Strategies to overcome these challenges include strengthening technology infrastructure, increasing digital literacy, providing financial and technical support, addressing data security issues, and actively driving digital transformation. By implementing this strategy collaboratively, MSMEs in Banda Aceh City can utilize the potential of digital technology to increase competitiveness, expand market reach, and contribute to economic growth in the Industry 5.0 era.